Numerical Investigation of the Low-Caloric Gas Burning Process in a Bottom Burner - Redko A.; Redko I. (Problems of the Regional Energetics)
The use of low-grade gases in the fuel and energy balance of enterprises makes it possible to increase the energy efficiency of technological processes. The volumes of low-grade gases (blast furnace and coke oven gases, synthesis gas of coal gasification processes, biogas, coal gas, etc.) that are utilized more significant in technological processes but their calorific value are low. At the same time artificial gases contain ballast gaseous (СО2, H2O) and mechanical impurities that are harmful gas impurities. Their use requires technological preparation. Thus coal methane is characterized of high humidity, coal dust and drip moisture, variable composition. Thus was effective burning of coal methane it is required the development of constructive and regime measures that ensure a stable and complete burning of gaseous fuels. In this article it is presented the results of computer simulation of a stationary turbulent diffusion flame in a restricted space in the process of burning natural gas and coal methane in a bottom burner. The calculation results contain the fields of gear, temperature, concentration of CH4‚ CO‚ H2O‚ CO2 and nitrogen oxides. The structural elements of the flame (recirculation zone, hot "dome", mixing layer and far trace) are determined. It has been established that complete combustion of coal methane in a modified bottom burner is ensured and the numerical values of nitrogen oxide concentrations in the flame are consistent with the literature data.